(De)constitution of the healthcare network of children/adolescents with special health care needs - Hentielle Feksa Lima; Diúlia Calegari de Oliveira; Caren da Silva Bertoldo; Eliane Tatsch Neves (Universidade Federal de Santa Maria, 2021)
Objective: to describe the use of services by children and adolescents with special health care needs (CSHCN) and its implications in the constitution of the healthcare network (HN). Methods: qualitative research carried out through interviews mediated by the Speaking-Map with 17 families of CSHCN in the first semester of 2019. The settings were the pediatric first-aid post and the pediatric admission unit of a teaching hospital. Data were submitted to inductive thematic analysis. Results: the themes that originated from the analysis were: Path taken to the articulation of the healthcare network of CSHCN and Challenges in the articulation of the healthcare network of CSHCN. The themes pointed out the discontinuity of the healthcare network of CSHCN. Conclusion: families of CSHCN do not have access to a consolidated reference and counter-reference flow at the healthcare networks and face constant peregrinations throughout the network searching for healthcare services.